2017
DOI: 10.1039/c7ra06233h
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of drug effects on HeLa cells by exploiting new AFM mechanical biomarkers

Abstract: New AFM mechanical biomarkers including cell brush length, adhesion work and the factor of viscosity are discovered for drug assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 40 publications
4
56
1
Order By: Relevance
“… 8 , 27 However, the cells treated with AgNPs present clear alterations in both morphology and number ( Figure 1 B,C), i.e., the cells tended to turn into a roundish shape and the cell density gradually decreased with increasing concentration of AgNPs, similar to the effect of graphene oxide sheets on HEK293T cells and other drugs or NPs on HeLa cells and/or MDA-MB-231 cells. 8 , 18 , 28 The morphological and inhibitory changes indicated that AgNPs are cytotoxic to HEK293T cells.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 8 , 27 However, the cells treated with AgNPs present clear alterations in both morphology and number ( Figure 1 B,C), i.e., the cells tended to turn into a roundish shape and the cell density gradually decreased with increasing concentration of AgNPs, similar to the effect of graphene oxide sheets on HEK293T cells and other drugs or NPs on HeLa cells and/or MDA-MB-231 cells. 8 , 18 , 28 The morphological and inhibitory changes indicated that AgNPs are cytotoxic to HEK293T cells.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the factor of viscosity is a much more meaningful physical parameter than the usually used Young’s modulus obtained by the Hertz–Sneddon model because cells are viscoelastic materials and, strictly speaking, cannot be modeled as an ideal elastic body using the Hertz–Sneddon model. 18 …”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth of the OTSpd chemical pattern provides a height reference for calculating the thickness of other parallel layer on itself. Although some studies applied AFM cross-section profile to analyze the height of object [ 28 30 ], it is believed that AFM topography histogram can better represent the average height change of pattern areas in the present work due to the protein film, which is immobilized on the chemical patterns, exhibiting an “unflat” surface. Histograms of the corresponding heights were fitted to two Gaussian functions by using MicroCal Origin software in order to enable a quantitative comparison.…”
Section: Methodsmentioning
confidence: 99%
“…As this method evolves over time, researchers have recognized the importance of integrating OEK with other devices/ tools to detect, analyze, and measure micro/nano-objects for biomedical and tissue engineering applications. This requires systematically combining OEK chips with other predominant micro/ nanorobotic-based techniques, such as atomic force microscopy, 119 acoustics tweezers, 120 and scanning ion conductance microscopy, 121 to achieve efficient 3D manipulation and multiparameter simultaneous acquisition, detection, and analysis of single cells.…”
Section: Challenges and Prospectsmentioning
confidence: 99%